PENERAPAN MODEL PEMBELAJARAN TPS (THINK PAIR SHARE) DALAM RANGKA MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA KELAS 3 (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2019)
The purpose of this study  is to improve the communication skills of students through the TPS (Think Pair Share) learning model. the results of observations show communication skills of grade 3 students in SDN Ledok 05 Salatiga is still low. the results of interviews with grade 3 teachers from 29 students in the High category only about 31% who dared to present or communicate in front of the class with confidence. While in the medium category only 24% and 45% of other students in the low category are still afraid if they get the opportunity to communicate to appear in public or in front of the class. The research method uses PTK (Class Action Research). Techniques for collecting data through observation, interviews, questionnaires. The instruments used are indicators of five components of interpersonal or interpersonal communication skills which include openness, empathy, supportive attitude, positive attitude, equality. Research uses quantitative descriptive. The results showed that the first cycle of the high category had a frequency of 18 with a percentage of 62%, medium category frequency 6 and a percentage of 21%, and a low category 5 with a percentage of 17%. Whereas for the second cycle the high frequency category was 20 with a percentage of 69%, medium category 8 with 28%, and low category 1 with a percentage of 3%. Class 3 communication skills at SDN Ledok 05 Salatiga increased after using TPS (Think Pair Share) models.